Padre Joaquin Garcia - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1984)
SPANISH: La fotografía muestra al padre Joaquin García ante un grupo de personas exponiendo las distintas actividades a realizarse por el festival del libro regional.
ENGLISH: The photograph shows Father Joaquin Garcia in front of a group of people explaining the different activities to be carried out for the regional book festival.

SPANISH: La fotografía muestra al padre Joaquin García ante un grupo de personas exponiendo las distintas actividades a realizarse por el festival del libro regional.
ENGLISH: The photograph shows Father Joaquin Garcia in front of a group of people explaining the different activities to be carried out for the regional book festival.
Father Joaquin Garcia
Keywords: S/N